'Insects as Food and Feed: If You Can't Beat Them, Eat Them!'—To the Magnificent Seven and Beyond. Issue 2 (3rd April 2021) - Rumbos, Christos I; Athanassiou, Christos G
Abstract: The objective of this special issue is to highlight the current state of research in the field of insects as food and feed, but also other aspects on the exploitation of insect farming. In this editorial, we make a short introduction of the topic of the special issue, briefly present the contributions that are collected in it and offer some thoughts on the future research priorities and challenges that should be addressed. Regarding insect farming, there are additional applications, such as fertilizer, health-promoting products, and cosmetics, that can be produced and utilized, that go far beyond food and feed production.